A PARAMETRIZATION OF RATIONAL D(q)-TRIPLES - Dražić, Goran (Matematichki Bilten, 2021)
We parametrize rational \(D(q)\)-triples for \(q Q\) which is not a square. We use this parametrization to describe all rational \(D(q)\)-triples which are also \(D(0)\)-triples, and to describe all rational \(D(q)\)-quadruples which contain at least one regular \(D(q)\)-triple.